Analisis Faktor Kinerja Bidan Dalam Pendokumentasian Buku KIA - Mawarti, Fitri; Podojoyo, Podojoyo; Ocktariyana, Ocktariyana (Publikasi Penelitian Terapan dan Kebijakan, 2025)
Background : To improve maternal and child health, the MCH (Maternal and Child Health) Handbook has been introduced as the primary tool for recording healthcare services. To identify the factors associated with midwives' performance in documenting the MCH Handbook used a cross-sectional design. Sample included all 33 midwives. Results: Bivariate analysis showed that knowledge level (p = 0.001), motivation (p = 0.002), and length of service (p = 0.005) were significantly associated with midwives' performance in documenting the MCH Handbook. In contrast, age (p = 0.162) and education level (p = 0.114) were not significantly associated. Conclusion: There is a significant relationship between midwives’ knowledge, motivation, and length of service and their performance in documenting the MCH Handbook. Socialization, orientation, and regular monitoring and evaluation are recommended to improve documentation practices. Keywords: midwife performance, knowledge, motivation, MCH Handbook